Byzantine burials at Abar el-Kanayis on the Marmarica-Plateau: a trace of anchorites in the Libyan Desert? - Großkopf, Birgit (Mitteilungen des Deutschen Archäologischen Instituts Kairo, 2016)
A Roman/Late Roman roadhouse stood at the cistern site of Abar el-Kanayis on the Marmarica-Plateau (Northern Libyan Desert), serving as a stopover on the route between the Mediterranean coast and Siwa. In a short phase of reuse after a sweeping fire in the 6th century CE, burials of at least four mature men were laid out in the rooms formed by newly erected walls. These burials allow for an interpretation as the tombs of Christian anchorites, who had retired to that place in the desert in Byzantine times